Simulation and Analysis of a Vehicle Chassis by ANSYS Program - Hasan, Mohammad; Abo Al-kibash, Taqi (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2019)
Automotive chassis, is the most important part of an automobile. The chassis serves as a framework for supporting the body and different parts of the vehicle, so it should be rigid enough to withstand the shock, twist, vibration and other stresses. Therefore, there are many criteria that must be taken into consideration when designing a chassis structure, where some of these criteria are what the manufacturers lay out for themselves when determining the characteristics of the chassis, and others criteria was based on the engineering design principles. As a result, strength and stiffness are two important criteria for the design of the chassis. Also, the weight of the chassis is an important consideration in chassis design due to its direct relationship with the amount of fuel consumption and the emissions rates, which emitted to the surrounding atmosphere. This project analyzing the structural design of a specific vehicle chassis by using the theory of finite element method (FEM), which performed by simulating the chassis model into a frontal car crash tests using ANSYS Workbench program. This project aims to achieve analytical results that will be recommended into a the next chassis design criteria, where it turns out that the cross-bridges, that the structure consist of, have a major role in mitigating the effect of the collision on the rest of the body of the vehicle. ا
no of pages 71 , ميكانيك 18/2019
Keywords: ANSYS Program; Vehicle Chassis